Fibroblast α11β1 integrin regulates tensional homeostasis in fibroblast/A549 carcinoma heterospheroids. - Ning Lu (Public Library of Science (PLoS), 2014)
We have previously shown that fibroblast expression of α11β1 integrin stimulates A549 carcinoma cell growth in a xenograft tumor model. To understand the molecular mechanisms whereby a collagen receptor on fibroblast can regulate tumor growth we have used a 3D heterospheroid system composed of A549 tumor cells and fibroblasts without (α11+/+) or with a deletion (α11-/-) in integrin α11 gene. Our data show that α11-/-/A549 spheroids are larger than α11+/+/A549 spheroids, and that A549 cell number, cell migration and cell invasion in a collagen I gel are decreased in α11-/-/A549 spheroids. Gene expression profiling of differentially expressed genes in fibroblast/A549 spheroids identified CXCL5 as one molecule down-regulated in A549 cells in the absence of α11 on the fibroblasts. Blocking CXCL5 function with the CXCR2 inhibitor SB225002 reduced cell proliferation and cell migration of A549 cells within spheroids, demonstrating that the fibroblast integrin α11β1 in a 3D heterospheroid context affects carcinoma cell growth and invasion by stimulating autocrine secretion of CXCL5. We furthermore suggest that fibroblast α11β1 in fibroblast/A549 spheroids regulates interstitial fluid pressure by compacting the collagen matrix, in turn implying a role for stromal collagen receptors in regulating tensional hemostasis in tumors. In summary, blocking stromal α11β1 integrin function might thus be a stroma-targeted therapeutic strategy to increase the efficacy of chemotherapy.